2017
DOI: 10.1186/s12986-017-0200-8
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia-induced oxidative stress and heart disease-cardioprotective effects of rooibos flavonoids and phenylpyruvic acid-2-O-β-D-glucoside

Abstract: Diabetic patients are at an increased risk of developing heart failure when compared to their non-diabetic counter parts. Accumulative evidence suggests chronic hyperglycemia to be central in the development of myocardial infarction in these patients. At present, there are limited therapies aimed at specifically protecting the diabetic heart at risk from hyperglycemia-induced injury. Oxidative stress, through over production of free radical species, has been hypothesized to alter mitochondrial function and abn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
79
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(80 citation statements)
references
References 229 publications
(228 reference statements)
1
79
0
Order By: Relevance
“…NO is broadly considered as one of the most vital molecules produced in the human body, and its acts as an essential regulator in a vast array of crucial physiological functions, especially the maintenance of vascular tone . Research over the years has led to the identification of several ROS generating systems that could potentially be modulated in conditions of hyperglycaemia . However, therapeutic approaches currently being used to improve cardiovascular function, including maintenance of vascular tone such as aspirin and statins present with limited antioxidant properties to protect against oxidative stress .…”
Section: Discussionmentioning
confidence: 99%
“…NO is broadly considered as one of the most vital molecules produced in the human body, and its acts as an essential regulator in a vast array of crucial physiological functions, especially the maintenance of vascular tone . Research over the years has led to the identification of several ROS generating systems that could potentially be modulated in conditions of hyperglycaemia . However, therapeutic approaches currently being used to improve cardiovascular function, including maintenance of vascular tone such as aspirin and statins present with limited antioxidant properties to protect against oxidative stress .…”
Section: Discussionmentioning
confidence: 99%
“…GPx is susceptible to free radical‐mediated OS, and it is obvious that in the present study, GPx activity is significantly decreased in H9c2 cells treated with high glucose concentration time‐dependently. Earlier reports have indicated that reduced GPx is responsible for hyperglycemia‐induced OS and heart disease …”
Section: Discussionmentioning
confidence: 99%
“…Lignans in barley have high anti-inflammatory abilities in endothelial cells by reducing nuclear factor-κB and extracellular signal as well as regulating kinase phosphorylation [156]. The polyphenols such as (+)-catechin, protocatechuate, and quercetin in barley not only have hepatoprotective effect [130] but also prevent coronary heart disease by reducing oxidativeinduced tissue damage through modulating intracellular signaling pathways [157]. Polyphenols play an important role in alleviating cardiovascular diseases due to their antiradical scavenging abilities [18].…”
Section: Polyphenols Mechanismmentioning
confidence: 99%